Ecuador’s 2025 presidential election and the disconnection between public health and the political agendas - Ortiz-Prado, Esteban; Terán, Enrique; Cuenca, Karla Alejandra; Echeverria, Julia Saa; Gallardo, Martín; Cadena, María Paz; Barriga, Mateo; Vasconez-Gonzalez, Jorge; Izquierdo-Condoy, Juan S. (Frontiers in Public Health, 2025)
BackgroundIn Latin America, public health proposals by presidential candidates often lack methodological rigor, limiting their feasibility and impact. Evidence-based planning aligned with national health priorities and disease burden is essential to address critical issues such as chronic diseases, mental health, and healthcare access.ObjectiveThis study evaluates the methodological robustness of public health policy proposals from 16 Ecuadorian presidential candidates for the 2025–2029 elections. The assessment focuses on key health variables, analyzing the presence of SMART objectives, epidemiological evidence, and alignment with local and global health priorities.MethodsA systematic evaluation framework was applied to analyze the health components of each candidate’s plan. The study used internationally recognized policy evaluation models, including the CDC’s Six-Step Policy Evaluation Framework and the UK Magenta Book Guidelines. Health variables were weighted based on national priorities, with percentage scores assigned according to alignment with GBD 2021 Ecuador data. Each proposal was assessed for inclusion or omission of these variables, allowing for a comparative ranking of methodological rigor.ResultsThe analysis of public health proposals from Ecuadorian presidential candidates revealed significant methodological deficiencies. A total of 81% of proposals lacked SMART objectives, limiting their ability to establish measurable goals. 76% failed to integrate key health determinants such as environmental health, intersectoral collaboration, and research funding. 92% did not include a defined financial strategy, raising concerns about feasibility. Only one candidate (Noboa/Pinto) scored above 50% compliance with the GBD Ecuador 2021 priorities. Mental health and infectious disease prevention were the most frequently addressed topics, while air pollution, food safety, and post-market drug surveillance were largely overlooked. Chronic disease care, environmental sanitation, and vaccine production were among the most underrepresented health priorities.ConclusionPublic health proposals from Ecuadorian presidential candidates (2025–2029) showed major methodological gaps, with 81% lacking SMART objectives and 92% lacking financial plans. Key areas such as neonatal care and non-communicable disease prevention were often omitted. A more systematic, evidence-based approach is needed, supported by collaboration between policymakers, researchers, and international health agencies.